The relationship of sprint performance to kinetic and kinematic variables during resisted swimming - Kuffel, Nicholas E. (My University, 2011)
Sport-specific resistance training relies on applying resistance to the same motions used in a sport's competition movements. Resisted swimming offers the opportunity to measure training variables used by coaches under an optimal force-velocity relationship. The purpose of this shtdy was to determine the relationship between kinetic and kinematic variables observed during resisted swimming and sprint performance. Three trials were conducted during weeks 1,6, and 12 (TI, T2, and T3) of the competitive season. During each trial week, a 45.72-m maximal effort freestyle sprint was used as a performance test. Two days later, 22.86-m resisted swim trials were performed against a predetermined resistance while recording and averaging time, strolce count, and stroke rate. A tethered swim test was used to determine peak force, average force, and the fatigue index of a maximal 30-sec maximum swim effort. A product-movement correlation determined the relationships of all variables to performance. The results show that peak and mean force were most strongly correlated to performance across all trials and genders. For coaches and athletes using resisted swimming, taking simple measurements of common training variables may provide some insight into the performance enhancing value of the training program being implemented.
Keywords: Muscle strength; Exercise -- Physiological aspects; Swimming -- Training